Assessing the Relationship Between Financial Ratios, Dividend Policy, and Stock Prices in Indonesia’s Pharmaceutical Industry - Pudjianto, Veny Christina; Widagdo, Bambang; Kholmi, Masiyah (University of Muhammadiyah Malang, 2024)
Pharmaceutical firms' performance has been optimized because of the rise of health conditions such as pediatric kidney failure, Acute Respiratory Infections, and the COVID-19 epidemic in recent years. Changes in pharmaceutical stock prices indicate market responses to the company's performance and policies. Financial reports can be used to evaluate a company's performance by calculating financial ratios like liquidity, profitability, and solvency ratios. This research quantitatively studies the associative type to determine the relationships between variables. The study sample includes 35 pharmaceutical companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2022. According to this research, stock prices are not influenced by profitability or liquidity. Solvency and dividend policy influence stock prices. This research also indicates that liquidity, profitability, and solvency do not influence dividend policy. Research indicates that the impact of liquidity, profitability, and solvency on stock prices cannot be mitigated by dividend policy. The company can effectively manage its capital structure and dividend policy in order to build and maintain shareholder trust because it is a consideration for shareholders when investing capital in the company.